Tracing the source of the Sparrow-Hawk Castle legend from John Mandeville's Travels - Bejanyan, Kristine H. (Имагология и компаративистика)
The plot of the Sparrow Hawk Castle, the fairy and the cursed Armenian king was first used by John Mandeville in his Travels, which became a source for Johann Schiltberger's The Bondage and Travels of Johann Schiltberger: a Native of Bavaria, in Europe, Asia, and Africa, 1396-1427, Jean of Arras's chivalric novel Mélusine, and Couldrette's The Romans of Partenay, Or of Lusignen: Otherwise Known as the Tale of Melusine. This article aims to identify the historical location of the castle-fortress and to uncover the source of its legend.